2021
DOI: 10.32598/bcn.2021.2634.1
|View full text |Cite
|
Sign up to set email alerts
|

Beta-amyloid Formation, Memory and Learning Decline Following Long-term Ovariectomy Are Inhibited by Systemic Administration of Apigenin and β-estradiol

Abstract: Objective: The increase in the number of patients with Alzheimer's disease (AD) has led to numerous problems. The risk of developing AD increases in menopause women. Apigenin and is β-estradiol are effective antioxidant and neuroprotective agents. In order to study the combined effects of them on beta-amyloid plaque formation, memory, and learning in ovariectomized rats, the present study was designed. Methods: Forty-two Wistar rats were randomly assigned into 7 groups; ovariectomized (OVX), OVX + apigenin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Their brain was removed and kept in graded sucrose solution as the cryoprotective agent, by using a freezing microtome (Leica 3000 Germany) and coronal sections of 10 μm were prepared. Nissl staining was done as mentioned in our previous studies (Hassanzadeh et al., 2018; Jameie et al., 2021). By using Image J software, the neuronal number and density of the hippocampus number were studied.…”
Section: Methodsmentioning
confidence: 99%
“…Their brain was removed and kept in graded sucrose solution as the cryoprotective agent, by using a freezing microtome (Leica 3000 Germany) and coronal sections of 10 μm were prepared. Nissl staining was done as mentioned in our previous studies (Hassanzadeh et al., 2018; Jameie et al., 2021). By using Image J software, the neuronal number and density of the hippocampus number were studied.…”
Section: Methodsmentioning
confidence: 99%
“…All the studies showed that apigenin improved learning and memory, except for two studies. From the Morris Water Maze tests, eight studies showed that apigenin reduced escape latency [20,30], improved the time spent in the target quadrant [26][27][28]30], reduced first entry to the target quadrant and increased the number of crossings into the platform region [27]. Only one study reported the effect of apigenin on spatial memory using the Barnes test.…”
Section: Learning and Memorymentioning
confidence: 99%
“…As one of the most frequently consumed flavonoids from the flavones subgroup, apigenin (4′,5,7-trihydroxyflavone) is present in the highest amounts in parsley, celery, mint, chamomile, lavender, apples, onions, oranges, lemons, broccoli, and spinach. It has a positive effect on learning, memory, and locomotor activity, as well as revealing anxiolytic properties, weaking depressive behaviors, and improving sensorimotor and motor coordination in animals with cognitive disease and neurobehavioral deficits [ 144 , 145 , 146 , 147 ]. It has been found that apigenin reduces the reactivity of microglia in the hippocampus, which is important in the initiation and progression of neurodegenerative diseases, such as AD [ 148 ].…”
Section: General Characteristics and Targets Of Flavonoidsmentioning
confidence: 99%